Lithofacies and sedimentary characteristics of the Silurian Longmaxi Shale in the southeastern Sichuan Basin, China - Jiang Zaixing (Journal of Palaeogeography, 2013)
The Silurian Longmaxi Shale (SLS) is the target for shale gas exploration and exploitation in the southeastern Sichuan Basin. Based on detailed description of cores and outcrops, analysis of Gamma Ray (GR) logs, thin sections and mineralogical data, the SLS can be subdivided into six lithofacies: (1) clayey shale, (2) siliceous calcareous shale, (3) siliceous dolomitic shale, (4) silty-clayey interlaminated shale, (5) muddy siltstone, and (6) graptolite shale. Three facies associations are recognized in the study area, i.e., inner shelf, outer shelf, and bathyal plain (including turbidite) facies. Outer shelf and bathyal plain facies dominate the lower interval of the SLS, while inner shelf facies dominates the upper part of the SLS. The thickness of the black shale in the northern part of the study area is the greatest, where siliceous calcareous shale, siliceous dolomitic shale, and graptolite shale are predominant. These three kinds of shale are rich in total organic carbon (TOC) content and brittle minerals, which is favourable for the accumulation of shale gas and its future exploitation.